Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2021
DOI: 10.1111/dme.14535
|View full text |Cite
|
Sign up to set email alerts
|

Young adults with type 1 diabetes and their experiences with diabetes follow‐up and participation in the DiaPROM pilot trial: A qualitative study

Abstract: Aim To explore young adults' experiences of outpatient follow‐up appointments, completing electronic Patient‐Reported Outcome Measures (PROMs), and using the Problem Areas In Diabetes (PAID) scale during the Diabetes Patient‐Reported Outcome Measures (DiaPROM) pilot trial. Methods We performed a qualitative study among 19 young adults (aged 22–39 years) with type 1 diabetes who participated in the pilot trial. Between February and June 2019, we conducted individual, semi‐structured telephone interviews with pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
33
0
2

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(40 citation statements)
references
References 27 publications
5
33
0
2
Order By: Relevance
“…In accordance with the current results, the researchers reported that their approach promoted reflective thinking and dialogue and facilitated patient-provider relationships and person-centeredness [ 42 ]. Another similarity between the results of the 2 studies is that the questionnaire scoring was enlightening for HCPs [ 42 , 43 ]. Satisfactory glycemic control can obstruct HCPs’ understanding of the patient’s situation, thus concealing significant challenges they face in everyday life.…”
Section: Discussionsupporting
confidence: 86%
See 2 more Smart Citations
“…In accordance with the current results, the researchers reported that their approach promoted reflective thinking and dialogue and facilitated patient-provider relationships and person-centeredness [ 42 ]. Another similarity between the results of the 2 studies is that the questionnaire scoring was enlightening for HCPs [ 42 , 43 ]. Satisfactory glycemic control can obstruct HCPs’ understanding of the patient’s situation, thus concealing significant challenges they face in everyday life.…”
Section: Discussionsupporting
confidence: 86%
“…In Norway, a related project investigated the assessment of diabetes distress in diabetes care for young adults with type 1 diabetes. This previous study used the Problem Areas In Diabetes (PAID) scale in conjunction with an empowerment-based communication manual to guide nurses in reviewing and discussing PAID scores [ 40 - 42 ]. In accordance with the current results, the researchers reported that their approach promoted reflective thinking and dialogue and facilitated patient-provider relationships and person-centeredness [ 42 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Vi har hittil gjennomført re delstudier i DiaPROM, alle ved Haukeland universitetssjukehus (18)(19)(20)(21). Målet med disse studiene var å teste gjennomførbarheten av intervensjonen og derved undersøke usikkerhet knyttet til å gjennomføre en fullskala randomisert kontrollert e ektstudie (RCT).…”
Section: Deltakerne Besvarte Spørsmålene Elektroniskunclassified
“…I den tredje studien intervjuet vi 19 unge voksne med diabetes type 1 som deltok i pilotstudien (20). Vi spurte om deres erfaringer med poliklinisk oppfølging generelt samt det å besvare elektroniske PROM og bruke PAID som dialogverktøy i konsultasjoner.…”
Section: Fire Delstudier I Diaprom Er Gjennomført Hittilunclassified